Efeito da suplementação de altas doses de vitamina D sobre a neuropatia autonômica cardiovascular em pacientes com diabetes mellitus tipo 1 - SILVA, Lilian de Souza d’Albuquerque (Universidade Federal do Pará, 2019)
Cardiovascular autonomic neuropathy (CAN), associated with diabetes mellitus (DM), despite being a subclinical condition, is an important morbidity and mortality factor in these patients. In type 1 diabetes mellitus (DM1) CAN is so alarming that it must be screened after the first 5 years of illness. Few therapeutic measures are recommended in international guidelines on the subject. Some authors have been studying drugs that can modified natural history of disease and then improve outcomes. Vitamin D seems promising resource and low cost. The aim of our study was to evaluate the effects of high-dose vitamin D (DV) supplementation on CAN in patients with DM1. We performed a prospective, interventional study in which 17 patients diagnosed with DM1 and CAN were included. Patients with VD levels below 30 ng / mL received 10,000 IU / day, and when 30-60 ng / mL, they used 4,000 IU / day. Serum VD dosage and CAN tests were performed before and after 12 weeks of treatment. There was an improvement in the parameters related to resting heart rate (HR) variability, which were: LF (1.9 ± 0.4 vs 2.2 ± 0.7 sec, p = 0.05), TP (2.5 ± 0.3 vs 2.7 ± 0.5 sec, p <0.05) , RRmax (0.8 ± 0.09 vs 0.9 ± 0.23 sec, p <0.05), RRNN (0.72 ± 0.09 vs 0.76 ± 0.09 sec, p <0.05) and SDNN (0.015 ± 0.005 vs 0.026 ± 0.018 sec; p <0.05). In addition, it was demonstrated that the variation of the RV level correlated with both the final HF (after treatment) and the LF / HF ratio (r = 0.57, p <0.05). Our pilot study is the first to suggest a strong association between high-dose vitamin D supplementation and improved cardiovascular autonomic neuropathy in DM1 patients. This occurred without any variation in HbA1C, blood pressure levels, lipids and insulin doses used